The Effect of Sex Reversal Using 17α-Methyltestosterone Hormones Towards The Colour Intensity of Male XX And Female XYFighting Fish (Betta Sp.) - Perbriansyah, Muhammad; Tarsim, Tarsim; Yulianto, Herman; Putri, Berta (AQUASAINS, 2016)
Fighting fish (Betta sp.) is endemic fresh water fish of Southeast Asia that has become one of Indonesias export commodities. Male fighting fish has brighter colour then the female. Mono-sexual male fighting fish population can be obtained through sex reversal method (female to male). However, male fighting fish suspected sex reversal results will likely have a low color intensity. This study aims to determine the effect of sex reversal using 17α-methyltestosterone hormone toward colour intensity of male fighting fish with XX genotype as the results of sex reversal and the original male fighting fish XY genotype. The research design consisted of 2 treatments with 3 replications. The determination of the observations grade toward the colour intensity of fighting fish is done by comparing the original colour of the fish using coloured paper Modified Toka Colour Finder (M-TCF) which were observed by 5 observers for the accuracy of the data. The results showed that there is significant effect of sex reversal using 17α-methyltestosterone hormone toward the colour intensity of the male fighting fish XX to XY males. On the whole, the mean observed colour intensity for P1 (with sex reversal) is 18.33 and P2 (without sex reversal) is 28.33, it shows that the P1 has lower brightness than P2.